Cover Feature: Comparative Study of Photoswitchable Zinc‐Finger Domain and AT‐Hook Motif for Light‐Controlled Peptide–DNA Binding (Chem. Eur. J. 19/2019). Issue 19 (12th March 2019) - Murawska, Gosia M.; Poloni, Claudia; Simeth, Nadja A.; Szymanski, Wiktor; Feringa, Ben L.
Abstract : Peptide DNA interactions are involved in gene expression. In this work, photoswitchable azobenzene moieties were implemented in the peptide backbone of a DNA minor‐ and a major‐groove binder. DNA binding affinity was affected by photochemical isomerization, which provides promising tools for DNA modulation. The cover art is inspired by light‐induced motion, here symbolized as dancing, in photoswitchable small peptides and their dynamic interaction with metal ions and DNA. Jana Volarić is thanked for her contribution to the design. More information on the research can be found in the Full Paper by W. Szymanski, B. L. Feringa, et al. onpage 4965 .